A new Neotropical species of Spercheus kugelann, and its larval stages (Coleoptera, Hydrophiloidea: Spercheidae) - Archangelsky, Miguel (2001)
Spercheus halophilus n. sp. is described together with its egg case and larval stages. This is the second Neotropical species for the genus. Comparative notes with adults of related species are included: S. halophilus seems closely related to S. fimbriicollis Bruch, 1915 and S. spangleri Hebauer, 1990. Larvae of S. halophilus show several important differences when compared with those of S. emarginatus (Schaller, 1783) and S. cerisyi Guérin-Meneville, 1842, most of them related to the mouthparts. This species lives in temporary pools of water gathered along the margins of roads running through a large salt flat in Central Argentina. Notes on the biology of this species are also included.